Unicystic ameloblastoma: An unusual case report - Ramya Mahalingam; Nandhini Gunasekaran; Dharani Bala; Dinesh Ravichandran; P Dhilipan; Dhivyaa Sivakumar (Wolters Kluwer Medknow Publications, 2020)
Ameloblastomas are the second most common tumor that originates from the odontogenic epithelium. The common age of occurrence is usually the third decade of life, with majority of the cases involving the mandible. Unicystic ameloblastoma accounts for about 5%-15% of all ameloblastic lesions with no tendency to metastasize. It is a slow-growing tumor but locally invasive with high rate of recurrence, especially the mural variant. We report a case of mural type of unicystic ameloblastoma in a 32-year-old female patient with added emphasis on its histopathological importance.